Analisis Hukum Islam Terhadap Praktik Bisnis Multi Level Marketing: Perspektif Fatwa DSN MUI dan NU - Jauhari, Muhammad Sofwan; Nugraha, Iqbal Subhan (STAINI Press, 2025)
This study examines the perspectives of the Indonesian Ulema Council (MUI) and Nahdlatul Ulama (NU) regarding Multi-Level Marketing (MLM) practices, focusing on the alignment with Islamic principles. MLM has gained popularity as a business model, but its compatibility with Islamic law has been debated, particularly concerning practices such as recruitment-based commissions and the potential for exploitation. This research uses a qualitative approach, analyzing fatwas and official statements from MUI and NU, as well as examining Islamic legal frameworks to assess the permissibility of MLM. The study finds that while MUI permits MLM under certain conditions, NU takes a stricter stance, condemning MLM that resembles pyramid schemes. The research highlights key elements that must be observed for MLM to comply with syariah, including transparency, fairness, and product legitimacy. The findings suggest that both organizations stress the importance of ethical practices in MLM, with the need for better regulation and public education to avoid exploitative systems.